SISTEM INFORMASI PENGOLAHAN DATA INVENTARIS BERBASIS WEB PADA UNIVERSITAS MUHAMMADIYAH JAMBI: Information Systems;Data Processing;Inventory;Web. - simorangkir, lucy; Hardiyanti Akhiria, Tri (LP2M Universitas Nurdin Hamzah, 2021)
Inventory is an activity and effort to provide records of the condition of facilities, items that have a laboratory. For educational institutions that have several laboratories it is very important to record facilities or inventory laboratory equipment and materials for activities, guidelines are obtained for preparing budgets or preparing for activities in the coming year, for example as learning. Muhammadiyah University (UM) is one of the universities in the city of Jambi in processing inventory data using Microsoft Word and there are several obstacles that are encountered, namely it is still difficult to record inventory. By paying attention to and also analyzing the problems faced, it is necessary to build a web-based information system with the aim of helping and making it easier for employees to be more efficient in processing equipment and goods inventory data quickly, accurately, on time, relevant and effectively so as to minimize errors. As small as possible and also optimize the performance of employees in the inventory of tools and goods. System input is in the form of inventory data, equipment and goods data, and transaction data. The data processing consists of the login process, the main menu display process, the inventory data menu display process, the tools and goods data menu display process, the transaction data menu display process, and the exit process. Output data in the form of goods data report. The expected result in this research is to make it easier to check the inventory data for tools and goods quickly and accurately.